PERENCANAAN POTENSI SUMBER DAYA KALI CIBEUTEUNG UNTUK EKOWISATA ARUNG JERAM Studi Kasus: Kali Cibeteung Desa Putat Nutug dan Kuripan, Ciseeng, Bogor, Jawa Barat - Prima Jiwa Osly; Fulki Dwiyandi Araswati; Akhmad Jarkasi Matondang; Daral Suraedi; Aryoseno Putra Wahyu; Okeu Aziz Maulana (Jurnal Infrastruktur, 2022)
Cibeuteung River is one of the rivers that is used as a tourist destination. The Cibeuteung River is a potential natural resource that can be developed as an ecotourism object and attraction. So this study aims to determine the identification of the potential of Cibeuteung river resources for rafting ecotourism, which is focused on knowing the characteristics of the rafting path, river slope, water discharge, river width and accessibility. This research uses survey method. Data was collected by using field observation and documentation techniques. Data analysis with descriptive analysis. The results showed that the river rafting route in Cibeuteung River has a river width of about 68 m to 98 m, a river slope of 0.5% to 0.3%, with a maximum discharge of 169.79 m3/s and a minimum of 26.03 m3/s. s in the dry season. Based on time, the starting point of the white water rafting route is 30 km (55 minutes) from downtown Bogor and 19 km (53 minutes) from downtown Depok. As well as from the analysis results Cibeuteung River has a start and finish point location that is easily accessible.